2017
DOI: 10.1038/s41598-017-01183-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of gonadotropin-inhibitory hormone in pubertal disorders induced by thyroid status

Abstract: Thyroid disorders cause abnormal puberty, indicating interactions between the hypothalamus-pituitary-thyroid (HPT) and hypothalamus-pituitary-gonadal (HPG) axes, which are important in pubertal development. The hypothalamic gonadotropin-inhibitory hormone (GnIH) was shown to be decreased in the early prepubertal stage, suggesting the role of GnIH on pubertal onset. Here, we investigated whether thyroid dysfunction affects pubertal onset in female mice via GnIH regulation. Hypothyroidism showed delayed pubertal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…Administration of thyroid hormone suppresses GnIH expression in hypothalamic explants, and GnIH neurons express thyroid hormone receptors to convey thyroid status. These findings indicate a novel function of GnIH to mediate interactions of the hypothalamic‐pituitary‐thyroid (HPT) and gonadal axes that contribute to pubertal regulation …”
Section: Regulation Of Pubertymentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of thyroid hormone suppresses GnIH expression in hypothalamic explants, and GnIH neurons express thyroid hormone receptors to convey thyroid status. These findings indicate a novel function of GnIH to mediate interactions of the hypothalamic‐pituitary‐thyroid (HPT) and gonadal axes that contribute to pubertal regulation …”
Section: Regulation Of Pubertymentioning
confidence: 99%
“…Kiyohara et al investigated whether thyroid dysfunction affects pubertal onset through GnIH in female mice. Hypothyroidism shows delayed pubertal onset with increased GnIH expression.…”
Section: Regulation Of Pubertymentioning
confidence: 99%
“…It was demonstrated that GnIH inhibits the adenylate cyclase (AC)/cAMP/protein kinase A (PKA)-dependent pathway both in GnRH neurons and gonadotropes (9, 10). The article further summarizes the mechanisms of how GnIH expression is regulated by glucocorticoid (18) and thyroid hormone (19). The third review article by Angelopoulou et al introduces that RFRP-3, mammalian GnIH, is involved in the central control of daily and seasonal rhythms of reproduction to synchronize reproductive activity to environmental challenges.…”
Section: Progress In Reproductive Neuroendocrinology In Vertebratesmentioning
confidence: 99%
“…Little is known about spatial‐temporal expression patterns and roles of GnIH during development because most published work focused on GnIH anatomical distribution and function in adult vertebrates . Even though some studies have evaluated GnIH (gene: gnih ) expression during embryonic stages in birds and mammals, the GnIH system has been examined to a greater extent throughout sexual development and the pre‐pubertal period . To our knowledge, only 3 studies have examined GnIH during fish development.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Even though some studies have evaluated GnIH (gene: gnih) expression during embryonic stages in birds and mammals, [15][16][17] the GnIH system has been examined to a greater extent throughout sexual development and the pre-pubertal period. [18][19][20][21][22][23][24][25] To our knowledge, only 3 studies have examined GnIH during fish development.…”
mentioning
confidence: 99%